Usulan Perbaikan Untuk Meningkatkan Produktivitas Proses Produksi Timbangan Weight Scale Dengan Metode Objective Matrix (Omax) Di PT. XYZ - Frena Fardillah; Muhammad Aqil Maulana (Journal Industrial Manufacturing, 2024)
This study aims to improve the productivity of the weight scale production process by using the Objective Matrix (OMAX) Method supported by Fishbone Diagram analysis and the 5W+1H approach. The weight scale is an important tool in various industries, so effectiveness and efficiency in the production process are very important. In this study, Fishbone Diagram is used to identify and analyze the main causal factors that affect productivity, such as people, machines, materials, methods, environment, and measurement. After observation, there are four factors that cause a decrease in productivity of weight scale products, namely human factors, materials, methods and machines. The 5W+1H approach was then applied to formulate appropriate improvement solutions based on the identified causes. The OMAX method was used to measure and monitor the effectiveness of the proposed improvements. The results show that the integrated application of these methods can reduce production cycle time, improve product quality, and increase overall productivity. This research makes an important contribution to the development of productivity improvement strategies that can be applied in various manufacturing sectors.Â Keywords: Productivity, Objective Matrix (OMAX) Method, Fishbone Diagram, 5W+1H, Process improvement